The Understanding of Islamic Thought as an Ideology and Methodology for the Indonesian Millennial Generation - WA Ode Sifatu (Universitas Muhammadiyah Metro, 2021)
This social study discussed the understanding of Islamic thought as a religious ideology and scientific methodology for the young Muslim generation who live, study, and work in a millennial time. There are many accusations and claims that Islam is a religion that only takes care of matters of religious ideology and worship and puts aside scientific and intellectual methodologies so that Islam is problematic to describe in the current context of the digital era by millennial generations in Indonesia as a country that is a big home for the world's largest Muslim adherents. To answer the above problems, we try to collect related literature. Then we study the phenomenological approach under the description of qualitative research design the work